A helping hand: examining the effect of foreign banks on the business environment. Issue 4 (21st September 2015) - Hartwell, Christopher A.; Michael, Bryane
Abstract : Purpose: – The penetration of foreign banks into emerging markets has been linked with financial sector deepening and expansion of credit. However, there is little research into the interaction of financial sector institutions with broader transition and development dynamics. The purpose of this paper is to examine if the presence of foreign financial institutions helped to shape a better business environment over the long-run in emerging markets. Design/methodology/approach: – The authors use aggregate, country-level annual data for 107 developed and emerging market countries over a shifting 30-year time span (1983-2012). The authors use Prais-Winsten and System-GMM techniques on stationary variables to highlight linkages between foreign banks and the overall business environment. Where data were found to be non-stationary, the authors applied panel cointegration approaches, including Granger Causality and full-modified OLS, to research the same relationship. Findings: – The results show that foreign bank entry in emerging markets has had a positive effect in the broader business environment, with the biggest effects on legal protection, competitiveness, and time to import/export. Research limitations/implications: – This paper does not consider the broader effects of foreign bank entry on competition within emerging markets, an area that the authors are considering as fruitful for future research. Originality/value: – The issue of financial sector impact on broader business environment issues has not been studied in the extant literature. Moreover, this study makes an important contribution for policymakers who are grappling with issues related to financial sector regulation in the post-global financial crisis world.